Ensuring Patient Safety through Patient Satisfaction: Factors Associated with Satisfaction Among Patients in OPD - Suja Kumari S , K T Moly , Aparna Rajesh , Abhirami. C , A Amalendu , Anju Yohannan (Migration Letters, 2024)
Introduction: In the present era, every patient has the right to expect the best possible care in hospitals, and hospital staff must make every effort to ensure patient satisfaction. Patient satisfaction is an essential determinant of healthcare quality. The Outpatient Department is the hospital’s first point of interaction with patients. Satisfied patients are more inclined to comply, which can lead to improved health results. Patient satisfaction influences high-quality health care’s prompt, effective, and client-centered provision. The study’s objectives were to determine the level of satisfaction and its associated characteristics among outpatient department patients. Method: A descriptive cross-sectional survey of patients visiting OPDs in a specific hospital was undertaken. The study’s data was gathered over three months. The sample size was calculated using the Danial sample size formula, and 424 people were chosen. After the OPD consultation, every third patient was picked. All participants in the study who chose to participate were given complete anonymity and secrecy. The Patient Satisfaction Questionnaire (PSQ-18) was used to determine patients’ satisfaction and the Satisfaction with Life Scale (SWLC). Results: Of the 424 participants, 46% reported that the waiting time was good, 44% said it was satisfactory, and 10% said it was poor. 77.4% of participants paid for their hospital bills. The majority (46.2%) were slightly satisfied, with only 10% extremely satisfied. The overall satisfaction was 22.74±4.98. Discussion: The patients’ overall degree of satisfaction was low. Gender, occupation, area of residence, family size, monthly income, accompanying person, time taken to reach the hospital, service seeking in hospital, pre-appointment facility, waiting time in OPD, accessibility of prescribed medicines, and availability of latrine, cafeteria, or refreshment facilities were associated factors of satisfaction (P<0.05). A key reason for patient dissatisfaction with the consultation process is a lack of interaction time with healthcare workers. Hence, patients and healthcare professionals need to improve effective communication. It is recommended that to improve patient safety, hospital administration and healthcare service providers assess the variables associated with patient satisfaction.